THE EFFECT OF GIVING PROPOLIS EXTRACT TO PREGNANT WOMEN WITH BACTERIAL VAGINOSIS - Kiki Apnita Sari; Willy Sandhika; Gatut Hardianto (Indonesian Midwifery and Health Sciences Journal, 2023)
Background: Bacterial Vaginosis (BV) in pregnancy is caused by several physiological changes that disrupt the vaginal ecosystem, namely hormonal changes and vaginal flora. Treatment with antibiotics for Bacterial Vaginosis (BV) cases has a risk of resistance, so alternative therapies are needed, one of which is propolis extract. This study aims to prove the effect of giving propolis extract to pregnant women with bacterial vaginosis. Methods: This study used a quasi-experimental type of clinical trial research with The Pretest-Posttest Control Group Design. The population in this study were 100 pregnant women who experienced flour albus at Anugrah Pratama Clinic Surabaya in September-December 2021. The sample of pregnant women with BV was 44 people who were divided into control and intervention groups. Independent variabel is giving propolis extract and dependent variabel is infection of bacterial vaginosis. The sampling technique in this study was consecutive sampling. Data analysis using Chi Square Test. Results: The control group did not reduce bacterial vaginosis infection, which remained with BV (+) infection by 54.5% and BV infection (-) by 45.5%, while the intervention group was proven to reduce bacterial vaginosis infection to BV infection (+) by 18 .2% and BV infection (-) of 81.8%. Analysis: The results of the Chi-Square test showed that the p-value of BV infection was 0.012 and bacterial vaginosis infection α (0.05). Conclusion: There is a significant difference between the control group and the group given propolis extract. It can be concluded that there is an effect of propolis extract administration on reducing infection in pregnant women with bacterial vaginosis.